Attending a concert reduces glucocorticoids, progesterone and the cortisol/DHEA ratio. (March 2016) - Fancourt, Daisy; Williamon, Aaron
Highlights: We examined the impact of attending a live, public concert on steroid hormone response in 117 participants. Participants provided saliva samples for hormone analysis prior to the concert and again at the interval 60 min later. There were significant changes in cortisol, cortisone, progesterone, cortisol/DHEA ratio and cortisol/cortisone ratio. This is the first evidence that attending a cultural event can have an impact on endocrine activity and down-regulate stress.